Credit Accessibility to Vulnerable Sections: Management Perspective - ., Veerashekharappa (Ushus Journal of Business Management, 2021)
Despite the vast expansion of the formal credit system in India, the dependence of the rural poor on informal credit institutions continues in some areas especially for meeting the emergency credit requirements. Such dependence is pronounced in the case of marginal farmers, landless labourers, petty traders and rural artisans, etc., particularly in the resource-poor areas. And credit needs of these sections determined in a complex socio-economic milieu, where it is difficult to adopt project lending approach as followed by banks and where the dividing line between credit for "consumption" and "productive" purposes is blurred (NABARD 1999). It is in this context, peoples' management in making credit to poor assumes significance. The participatory approach bring out the mutual trust and over comes the asymmetric information between the members, which is necessary for initiating banking relationship based on trust and confidence.